Effects of elevated atmospheric ozone concentration on biomass and non-structural carbohydrates allocation of cherry radish - Li, Li; Yang, Bingkai; Li, Jinling; Wang, Xiaoke; Ullah, Sami (Frontiers in plant science, 2025)
Regional increases in atmospheric O 3 have phytotoxicity due to its strong oxidizing properties. Cherry radish ( Raphanus sativus L.), with its sensitivity to O 3 and rapid growth cycle, serves as an excellent model for investigating the effects of elevated O 3 on plant physiological responses. To determine the response of cherry radish to elevated O 3 levels, we used nine open-top chambers with three O 3 concentrations (Ambient-LO; 70 ppb O 3 above ambient-MO; 140 ppb O 3 above ambient−HO) in Beijing, China to examine the MDA, chlorophyll contents, biomass, soluble sugar, and starch contents in response to O 3 exposure. The results showed that: 1) elevated O 3 (EO 3 ) did not affect leaf chlorophyll contents but increased carotenoid contents; (2). The total biomass, hypocotyl biomass and hypocotyl size were significantly decreased by 41% and 49%, 51% and 37%, 53% and 40% by MO and HO, respectively. The above-to-below-ground biomass ratio (A/B) increased by 49% and 61% under MO and HO treatments; (3). HO and MO significantly increased leaf fructose, sucrose, and glucose contents by 192% and 79%, 40% and 37%, 110% and 45%, respectively; (4). leaf soluble sugar biomass proportion increased by 75% and 99% under HO and MO mainly contributed by fructose biomass proportion increase; (5). radish plant allocated more soluble sugar, starch and NSC biomass proportion to leaf but not hypocotyl under EO 3 . In conclusion, radishes exposed to O 3 allocate more nonstructural carbohydrates (NSC) to the leaf at the expense of a great loss of hypocotyl biomass. This is possible mainly due to compensation of O 3 -induced damage via the sugar transport pathways, where transport is blocked so that the inefficient conversion of soluble sugars into starch can lead to reduced biomass accumulation and ultimately lower crop yields of radish. The role of radish fructose in protecting against or responding to O 3 risks may be underestimated as it affects the overall sugar metabolism and transport within the plant.